2021
DOI: 10.1039/d0sc05614f
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hidden halogen mobility on local structure of CsSn(Cl1−xBrx)3 mixed-halide perovskites by solid-state NMR

Abstract: Unravelling the atomic-level chemical structure, slow phase conversion or degradation pathways and rapid halogen hopping of cesium tin(ii) halide perovskites using solid-state 119Sn and 133Cs NMR spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
79
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(91 citation statements)
references
References 77 publications
11
79
1
Order By: Relevance
“…For instance, Snbased MHPs oen degrade within minutes of ambient exposure, for which acquisition of multidimensional ssNMR experiments is less straightforward. 185,312,313 Acceleration of acquisition times for ssNMR experiments, particularly for masslimited samples such as thin lms, have been pivotal for the characterization of MHPs. 314 The length scales of physical interactions in MHP devices span from the unit-cell ( A) scale to many cm.…”
Section: Length and Timescales Of Physical Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Snbased MHPs oen degrade within minutes of ambient exposure, for which acquisition of multidimensional ssNMR experiments is less straightforward. 185,312,313 Acceleration of acquisition times for ssNMR experiments, particularly for masslimited samples such as thin lms, have been pivotal for the characterization of MHPs. 314 The length scales of physical interactions in MHP devices span from the unit-cell ( A) scale to many cm.…”
Section: Length and Timescales Of Physical Processesmentioning
confidence: 99%
“…The environmental stability and degradation processes of a wide variety of 3D MHPs have been investigated by multinuclear ( 1 H, 207 Pb, 119 Sn, 133 Cs) ssNMR spectroscopy techniques. 312,313,359,367,368 The hydrothermal stability and degradation of MAPbI 3 has been characterized through 1D 207 Pb NMR spectroscopy, and revealed that pristine MAPbI 3 and its degradation products, MAPbI 3 $H 2 O, and PbI 2 , have distinct chemical shis (Fig. 7a).…”
Section: Cations Anions and Degradation Products In 3d Mhpsmentioning
confidence: 99%
See 1 more Smart Citation
“…133 Cs sensitivity towards variations in the local environment is also exploited in NMR analysis of lead-free perovskites [ 83 ]. The transition from the cubic to the monoclinic phase for CsSnCl 3 is easily monitored over time, as the 133 Cs NMR resonance of the two forms differs in position and linewidth ( Figure 3 b).…”
Section: Bulk Perovskitesmentioning
confidence: 99%
“…12,13 The tin(II) halide perovskites ASnX3 are possible alternatives with lower toxicity, but they exhibit lower PCE of up to 10% and rapidly oxidize in air (Sn 2+ to Sn 4+ ). [14][15][16][17] Vacancy-ordered double perovskites A2BX6 (A = Cs + , CH3NH3 + , CH(NH2)2 + ; B = Sn 4+ ; X = Cl − , Br − , I − ) are an alternative family of perovskites, demonstrating much higher ambient stability and lower toxicity. 18 The structure of A2BX6 can be described as an ABX3 perovskite, with half of the Bsites removed in an ordered fashion (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%